(untitled) (Bangladesh Journal of Livestock Research, 2022)
The present study was conducted to evaluate the cattle genotype and their distribution pattern, socio-economic status of the farmers, existing cattle breeding strategies and their facilities to understand the cattle breeding scenario in Netrokona district, Bangladesh. A total of 80 farmers (8 farmers from each upazilla) were surveyed from 10 Upazillas in Netrokona district. Each farmer’s gender, age, educational level, family size, income, number of family members involved in cattle rearing, cattle genotypes and breeding practices of the cattle were assessed in-depth. The results of the survey study revealed that 85% farmers were males and 15% farmers were female in the respective area. The majority of farmers (55.84%) had a medium size farm having 4-6 number of cattle per family. Within the surveyed region 83.12% farmers practiced artificial insemination (AI) for cattle breeding, whereas 16.88% still practiced natural mating by using their own bulls. In the study areas, the majority of farmers (75%) considered AI to be simpler than natural mating. While choosing bull for breeding services, Holstein-Friesian cross (31.18%) was first priority for the farmers followed by Sahiwal cross (20.35%), local (18.21%), Red Chittagong cattle (11.69%), Brahman (8.22%), Red Sindhi (5.19%) and Jersey (4.76%) respectively. In conclusion, this study on the current scenario of cattle breeding practices in Netrokona district provides valuable insights on major constrains and prospects of cattle breeding scenario in Netrokona district that can inform targeted interventions and policies, fostering sustainable and improved outcomes for the improvement of cattle breeding strategy for the local farmers. Bang. J. Livs. Res. Vol. 29 (1&2), 2022: P. 53-61